Activities of cytochrome P450 enzyme CYP102A16 from Bacillus sp. C3 - LI Ze-li; DING Hai-tao; YANG Yu-yi; CHEN Xue-jiao; ZHAO Yu-hua; ZHOU Qi-fa (浙江大学学报. 农业与生命科学版)
Cytochrome P450 monooxygenases (P450s or CYPs) belong to a large family of hemoproteins which are widely distributed among various organisms ranging from eukaryotes to prokaryotes. P450s play a pivotal role in the biosynthesis of bioregulators such as prostaglandins, leucotrienes and steroid hormones, and participate in the metabolism of xenobiotic such as poisons, drugs, and environmental pollutants. In recent years, more and more researches reported that P450s were potentially useful in the environmental remediation. And bacterial CYPs have been found to be more promising than those from plants and animals because of more solubility and higher stability, not membrane-associated and higher reaction rates. However, the activity of wild type prokaryotic P450s towards recalcitrant contaminants has been less reported as compared to eukaryotic P450s.In our laboratory, a novel cytochrome P450 monooxygenase CYP102A16, which belonged to CYP102 family, was cloned from Bacillus sp. C3 and expressed in Escherichia coli. CYP102 family represents a bacterial P450 one naturally fused with cytochrome P450 and cytochrome P450 reductase, making them potentially more useful in biotechnological applications due to their self-sufficiency, while the reaction catalyzed by cytochrome P450 requires cytochrome P450 reductase for transfer electron. The recombinant CYP102A16 was then purified by Ni-NTA affinity chromatography. The effects of temperature, pH, organic solvents, surfactants, metal and non-metal ions on the activity and stability of purified CYP102A16 were investigated based on nicotinamide adenine dinucleotide phosphate (NADPH) oxidation assay.The results showed that the optimum pH for CYP102A16 was 6.5-7.5, with a highest NADPH consumption rate of (885.5±11.7) U at pH 7.5 in Tris-HCl buffer (Fig. 1C). CYP102A16 was stable under a wide range of pH, retaining more than 80% of its activity after incubated at pH 5.0-10.0 for 30 min (Fig. 1D). The enzyme reached a highest activity of (511.0±20.5) U at 35 ºC, and kept stability at the temperatures below 45 ºC with residual activity of above 95% (Fig. 1A, B). CYP102A16 was completely stable in 20% dimethylsulfoxide (DMSO), 30% methanol, 10% ethanol and 20% acetone, and could retain above 45% activity in 10% acetonitrile, n-propanol and isopropanol, but was almost inactivated in 10% n-butanol (Table 1). The enzyme activity increased about 40% and 60% when low levels of cetylpyridine chloride (CPC) (0.003-0.02 g/L) and Triton X-100 (0.1-0.2 g/L) were added respectively, while non-significant effect was found with the addition of low concentration of sodium dodecyl sulphate (SDS) (0.004-0.008 g/L). The activity decreased gradually with increasing the surfactant concentration, and it was almost inactivated at 0.09 g/L CPC, 5.0 g/L Triton X-100 or 0.08 g/L SDS (Fig. 2). Addition of 1-20 mmol/L K+, 20-50 mmol/L Na+ and 0.05 mmol/L Cd2+ increased CYP102A16 activity slightly, while NH4+, Ca2+, Mg2+, Fe3+, Co2+, Mn2+, Zn2+, Cu2+ and ethylene diamine tetraacetic acid (EDTA) exhibited negative effects on enzyme activity (Fig. 3). Inhibition at 1-100 mmol/L concentrations was observed by the order of Ca2+ > Mg2+ > NH4+ > EDTA, and the effect was positively correlated with the concentration of metal and non-metal ions.Exploration of the in vitro catalytic conditions for CYP102A16 provides a reliable basis for constructing a better in vitro catalytic system for CYP102A16, which is of significant importance for its practical application in environmental remediation.